Disease burden and risk factors of ischemic heart disease in China during 1990–2019 based on the Global Burden of Disease 2019 report: A systematic analysis - Li, Yanting; Zhang, Jun (Frontiers in Public Health, 2022)
Objective: A systematic analysis of the disease burden and risk factors of ischemic heart disease (IHD) in China, 1990-2019, for the global burden of disease (GBD) 2019. Methods: The rates of incidence, death, years of lost life (YLLs), years lived with disability (YLDs), and disability-adjusted life years (DALYs) of IHD were available from GBD2019 to reflect the disease burden and risk factors of IHD in China. Results: In 2019, the YLDs rate of IHD in Chinese female was higher, while the rates of incidence, death, YLLs and DALYs in Chinese female were lower than those of male. The disease burden of IHD has significant age differences, and people aged ≥70 years with a highest disease burden. A total of 24 risk factors were related to the death and DALYs rate of IHD, and the top 5 were high systolic blood pressure, high LDL cholesterol (LDL-C), smoking, ambient particulate matter pollution, and diet high in sodium. The rates of incidence, death, YLLs, YLDs, and DALYs of IHD in China, 1990 to 2019, have increased at different levels. The annual rate of change of incidence, death, YLLs, YLDs and DALYs rates of IHD were 1.31%, 1.57%, 0.93%, 1.14% and 0.94%, respectively. Ambient particulate matter pollution (4.08%), high body-mass index (BMI, 3.3%), and diet high in processed meat (2.39%) resulted in a high annual rate of change in death rate during 1990 to 2019. Ambient particulate matter pollution (3.06%), high BMI (2.57%), and diet high in processed meat (1.79%) led to an increased annual rate of change in DALYs rate from 1990 to 2019. DALYs rate of 11 IHD risk factors were increased, while 8 risk factors were decreased. Conclusion: The disease burden of IHD in China was continuing to rise, especially in people aged ≥70 years old. The main disease burden of IHD on male patients was premature death, and the burden on female patients was mainly caused by disability. Therefore, periodic health check-up and high-risk factors intervention for key populations should be strengthened from the grassroots level, which is conducive to further reducing the disease burden of IHD in China.